Molecular investigation of pediatric Portuguese patients with sensorineural hearing loss - Nogueira, Célia (2012)
Introduction Sensorineural hearing loss (SNHL) is one of the most common disabilities in human, and genetics is an important aspect in research and clinical practice for SNHL. One in 1000 children is born with bilateral SNHL, and 50-70% of them have monogenic causes for their deafness. Hereditary hearing loss can be classified into syndromic and nonsyndromic depending on the associated features. Whilst over 400 genetic syndromes have been described in association with mono- or bilateral deafness, syndromic conditions account for about 30% of hereditary congenital hearing loss whereas the relative contribution to all deaf people is much higher (>70%) for nonsyndromic subtypes. The understanding of the molecular genetics in SNHL has advanced rapidly during the last decade but the molecular etiology of hearing impairment in the Portuguese population has not been investigated thoroughly. Methods We analyzed the whole mitochondrial genome in 95 unrelated children with SNHL (53 non-syndromic and 42 syndromic) and searched for variations in two frequent mutated genes, GJB2 and GJB6, in the non-syndromic patients. Results Mutations in mtDNA were detected in 4.2% of the cases, including a hitherto undescribed change in the mtDNA-tRNATrp gene (namely, m.5558A>G). We also identified mono- or bi-allelic GJB2 mutations in 20 of 53 non-syndromic cases and also detected two novel mutations (p.P70R and p.R127QfsX84). Discussion Our data suggest that analysis of the GJB2 gene may have clinical implications in the diagnosis of deaf Portuguese children. Also, it would make feasible early rehabilitation and prevention in affected families. The relatively higher incidence of mtDNA mutation also suggests that screening for variations in the mitochondrial genome should always be considered unless mitochondrial inheritance can be excluded for certain. The molecular diagnosis will permit more accurate genetic counseling for family members, monitor possible multisystem complications, and avoid usage of aminoglycosides if infections occur.